2013
DOI: 10.1016/j.ajpath.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MHC Class I in Muscle of Lymphocyte-Deficient Mice Causes a Severe Myopathy with Induction of the Unfolded Protein Response

Abstract: Muscle fibers do not normally express major histocompatibility complex class I (MHC-I) molecules, and their reexpression is a hallmark of inflammatory myopathies. It has been shown in mice that overexpression of MHC-I induces a poorly inflammatory myositis accompanied by the unfolded protein response (UPR), but it is unclear whether it is attributable to T-cell-mediated MHC-I-dependent immune responses or to MHC-I forced expression per se. Indeed, besides presenting antigenic peptides to CD8(+) T cells, MHC-I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…Muscle tissue from the murine H-2k b myositis model and from patients with myositis, displays ER stress-related markers such as increased Grp78 and Caspase12 8 22. Additional examination of the H-2k b murine model, which was generated to be immunodeficient, demonstrated profound muscle weakness, which further supports the hypothesis that non-immune mechanisms (eg, ER stress) could play a key role in muscle dysfunction in IIM 23. A recent study of muscle biopsies from patients with myositis confirmed colocalisation of the ER stress-related proteins Grp75 and Grp94, within fibres which show upregulated levels of MHC-I 8 24.…”
Section: The Potential Role Of Er Stress In Iimmentioning
confidence: 54%
“…Muscle tissue from the murine H-2k b myositis model and from patients with myositis, displays ER stress-related markers such as increased Grp78 and Caspase12 8 22. Additional examination of the H-2k b murine model, which was generated to be immunodeficient, demonstrated profound muscle weakness, which further supports the hypothesis that non-immune mechanisms (eg, ER stress) could play a key role in muscle dysfunction in IIM 23. A recent study of muscle biopsies from patients with myositis confirmed colocalisation of the ER stress-related proteins Grp75 and Grp94, within fibres which show upregulated levels of MHC-I 8 24.…”
Section: The Potential Role Of Er Stress In Iimmentioning
confidence: 54%
“…MHC-I molecules are necessary for antigen-specific T cell-mediated cytotoxicity and can mediate a response against surface antigens on myofibres [10]. Previous studies have also shown that MHC-I can behave as a pathogenic molecule in its own right since its expression can precede lymphocytic cell infiltration, and transgenic mice overexpressing MHC-I have been shown to develop a severe myopathy even in the absence of inflammation [11][12][13][14]. Unlike the inflammatory infiltrates, MHC-I expression is still detectable even after short-term immunosuppressive treatment and in patients with chronic myositis [9,15].…”
Section: Mhc-i Is Expressed But Is Undetectable Immunohistochemicallymentioning
confidence: 99%
“…However, recent studies have shown that MHC-I overexpression can also mediate muscle fibre damage and dysfunction even in the absence of inflammation, through non-immune mechanisms such as endoplasmic reticulum (ER) stress and induction of the unfolded protein response [11,26,27]. This could explain the incomplete efficacy of immunosuppressive drugs in the treatment of IIM and the disparity between the severity of muscle damage and extent of inflammatory infiltrates in muscle biopsies, as well as the increased MHC-I expression in non-inflammatory myopathies.…”
Section: Text 14mentioning
confidence: 99%
“…A recent mouse study has highlighted the potential importance of ER stress above inflammation in mediating IIM. Thus, even in a immunodeficient version of the H2-k b murine model of myositis, that is, ER stress-induced myopathic changes and muscle weakness still occurred in the absence of significant inflammatory cell infiltrations [20]. Collectively, these data suggest that activation of the ER stress pathway has an important role to play in the induction of nonimmune cell-mediated muscle weakness a process which may also apply in human IIM.…”
Section: Key Pointsmentioning
confidence: 83%